What are the factors affecting survival after autologous stem cell transplantation in patients with multiple myeloma? - Solmaz, Şerife; Acar, Celal; Seyhanlı, Ahmet; Sevindik, Ömür Gökmen; Pişkin, Özden; Özcan, Mehmet Ali; Demirkan, Fatih; Ündar, Bülent; Alacacıoğlu, İnci; Özsan, Güner Hayri (Wolters Kluwer Medknow Publications, 2020)
Introduction: High-dose chemotherapy (HDC) and autologous stem cell transplantation(ASCT) still remains in the treatment of myeloma patients even during the period of new agents. Materials and Methods: We analysed the prognostic affect of pretransplant characteristics and transplant modalities on response, in 150 autologous transplant of 144 multiple myeloma (MM) patients who were transplanted in our centre between 2008 to 2017. We evaluated the affect of age, type of MM, previous treatment regimens, status pre and postfrom transplantation, time of ASCT, neutrophil and platelet engraftmant days, dose of reinfused CD34+ cells, plasma cell infiltration, international staging system(ISS) and Durie -Salmon stage at diagnosis. We examined the affect of these status on overall survival(OS) and eventfree survival(EFS). Results: The median OS and EFS after transplanation were 41 and 28 months, respectively. Median OS after the diagnosis was 57 months. Transplant-related mortality was 3,3%. We found that the lower beta 2- microglobulin levels,lower ISS stage,lower plasma cell infiltration, achievement good responds at the +100th day of post transplant were statistically significant independent predictor factors for longer EFS and OS. When the patients were given chemotherapy regimen with bortezomib before transplantation, these patients were seen to be a better response rate. There was showed a relationship between the using of bortezomib before transplantation with EFS(P = 0.017), but there was no relationship with OS. Conclusions: Our analysis confirms HDCT-ASCT as an effective and safe therapeutic strategy in multiple myeloma patients. This results were independent of age, first line treatment regimens and renal insufficiency. Patients with a high ISS stage were found to have shorter survival(P = 0.002). However, the EFS and OS were longer of the patients whose have good response at the 100th day of transplantation(P = 0,002, P = 0,02).
Keywords: Autologous Stem Cell Transplantation; Event-Free Survival; Multiple Myeloma; Overall Survival